Development of Focusky Multimedia-Based Comics to Increase Students' Learning Interest in Science Subjects - Siti Fatimah; Siti Fatonah (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to find out the process of developing comics based on focusky multimedia. To determine the feasibility of focusky multimedia-based comics to determine the effectiveness of focusky multimedia-based comics to increase student learning interest. This research is an R&D development research or (Research and Development) model of the Robert Maribe Branch using the ADDIE development model. Data collection techniques used are observation, interviews, documentation and questionnaires. Qualitative data analysis was carried out by processing data obtained by validation questionnaires from media experts, material experts, linguists and peer assessments. While the quantitative data were processed by analyzing the pre-requisite normality test and paired sample t-test. The subjects in this study were 20 students of SD Al-Qur'an Rodlotut Tholibin Metro Lampung. From the research results, digital comic media was developed using the ADDIE model, namely Analysis, Design, Development, Implementation, Evaluation. The quality and feasibility of developing comics based on multimedia focusky were obtained from the validation assessments of media experts, material experts, linguists as well as assessments from colleagues, namely with ideal percentages of 88, 90, 86 and 86%, which were categorized as "very feasible" and can be considered. implement in learning. After analyzing the data obtained, it was successful in developing multimedia-based comics focused on natural science material, sub-theme of how the body processes food. Based on the results of the research, the paired sample t-test (one group sample test) with the results on students' interest in learning obtained a Sig. (2 tailed) of 0.000 <0.05. With an average pretest score of 53.30 it increases the results of posttest learning interest with an average score of 78.60